2017
DOI: 10.1080/22423982.2017.1398009
|View full text |Cite
|
Sign up to set email alerts
|

High tobacco use prevalence with significant regional and sex differences in smokeless tobacco use among Western Alaska Native people: the WATCH study

Abstract: Tobacco use prevalence among Alaska Native (AN) people living in Alaska is greater than the general population prevalence statewide and nationally. Better understanding of regional tobacco use is needed to improve cessation efforts and reduce prevalence. Using self-reported baseline data from the Western Alaska Tribal Collaborative for Health study, we describe tobacco use patterns among AN people in two western Alaska regions. Data were stratified by age group and sex. Dual- and multi-product use in the Yukon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Dual tobacco use in our sample was more common among younger than older adults and among males than females. While prior research has identified younger age and gender in association with dual tobacco product use 11,12 , a study of Western Alaska Native people found greater dual use among females than males, with particular high prevalence of Iq'mik use among the women in their sample 12 . Differences in findings by gender may be due to regional differences in tobacco product use.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Dual tobacco use in our sample was more common among younger than older adults and among males than females. While prior research has identified younger age and gender in association with dual tobacco product use 11,12 , a study of Western Alaska Native people found greater dual use among females than males, with particular high prevalence of Iq'mik use among the women in their sample 12 . Differences in findings by gender may be due to regional differences in tobacco product use.…”
Section: Discussionmentioning
confidence: 95%
“…Notably, 49.3% of Alaska Native adults in the Norton Sound region of Alaska smoke cigarettes compared to 39.0% among Alaska Native adults in Alaska's southwest Yukon-Kuskokwim region 7 ; whereas smokeless tobacco use prevalence in Norton Sound is lower (10.4%) than that in the Yukon-Kuskokwim region (37.5%) 9 . Among all adults in Alaska who smoke, 10% report dual tobacco product use 8 , while estimates of dual use among Alaska Native people who smoke range from 3.0% to 11.0%, differing by region and demographic characteristics [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…The use of tobacco among pregnant and nursing mothers is a ubiquitous and hazardous problem worldwide and it is becoming increasingly recognised that these effects are not limited to affecting the health of the mother but also the foetus and child. The predominant source of tobacco is cigarette smoking, but chewing tobacco is more frequent among fertile women in some regions, for example India and Alaska . Other sources of nicotine, such as e‐cigarettes, waterpipes and smokeless tobacco, are an increasing problem among pregnant women in the USA .…”
Section: Discussionmentioning
confidence: 99%
“…The data set is comprised of three population-based studies initiated in two adjacent western Alaska regions during 2000–2004: the Genetics of Coronary Artery Disease in Alaska Natives (GOCADAN) study ( Howard et al, 2005 ) based in the Norton Sound region, and the Centers for Alaska Native Health Research (CANHR) ( Mohatt et al, 2007 ) and Education and Research Towards Health (EARTH) ( Slattery et al, 2007 ) studies based in the Yukon-Kuskokwim Delta (Y-K) region. All self-reported tobacco use data were either combined directly or harmonized and redefined to incorporate slight differences in collection methods, questions, and/or response options, as described in Koller et al (2017) . The consolidated data set provides a unique opportunity to study age of tobacco initiation among AN people living in these two rural western Alaska regions.…”
Section: Methodsmentioning
confidence: 99%